Genetic studies on congenital heart disorders - Aparicio Sánchez, José Juan (2020)
Congenital heart defects represent the most common form of congenital abnormality. These developmental disorders affect at least 4000 new-borns each year in the UK, and present an incidence of approximately one in every 100 babies born. The most common cause for CHDs are genetic mutations that are inherited or arise de novo during embryogenesis, and even though we have gained great insight into the CHD-causative genes during these last decades, we are still far from understanding the whole picture. In this PhD thesis, my main goal is to contribute to the genetics of congenital heart disorders by discovering and characterizing new factors involved in cardiac development and in the onset of CHD. During this thesis, I have worked on three different projects whose results have ultimately contributed to this field.